Pengaruh Experiential Marketing terhadap Niat Mengunjungi Kembali di Rumah Makan dengan Kepuasan Konsumen sebagai Variabel Mediasi - Nourissa Dinda Syachadi; Widyastuti Widyastuti (Jurnal Ilmu Manajemen, 2021)
This research aims to determine the effect of experiential marketing on the revisit intention at Si Bolang restaurant and customer satisfaction as mediation variables. The population is the customer of Si Bolang restaurant, with a total of respondents 200. The study method is quantitative and data collection using Google Forms online questionnaire. Data analysis used is Path analysis with SPSS version 25 program, and the variables used included experiential marketing, customer satisfaction, and revisit intention. Data analysis conducted are validity, reliability, path analysis, and Sobel. This research shows a significant effect of experiential marketing on revisit intention; subsequently, customer satisfaction has a significant effect on the revisit intention. Next, experiential marketing has a significant effect on revisit intention, and this study concludes that it is proven that customer satisfaction has a role as a mediation variable between experiential marketing and revisit intention. This research is based on current conditions making eating necessary to meet hunger and turning into culinary tourism with lifestyle changes, making the restaurant industry marketing activities focus on atmosphere, design, hospitality, and other intangible factors. It is necessary to pay attention to strategies in providing experiences to consumers, such as improving the taste of food, developing menus, increasing food presentation, increasing restaurant concepts and improving service in order to increase comfort in dining such as eating at home, so that grow a sense of satisfaction and provide encouragement to consumers' intentions to make repeat visits.